Neogene Pectinidae (Bivalvia) of tribe Chlamydini in Patagonia (Argentina): Zygochlamys and three new genera - Santelli, María Belén; del Río, Claudia Julia (Journal of Paleontology)
Zygochlamys Ihering, 1907 is revised and three new genera of tribe Chlamydini are named: the monospecific early Miocene genera Pixiechlamys new genus (type species: Pecten quemadensis Ihering, 1897) and Chokekenia n. gen. (type species: Zygochlamys nicolasi Morra, 1985), and the late Miocene-early Pliocene Moirechlamys n. gen., containing Pecten actinodes Sowerby, 1846 (type species) and Chlamys auroraeFeruglio, 1954. Zygochlamys is restricted to include Z. geminata (Sowerby, 1846) (type species), Z. jorgensisIhering, 1907, and Z. sebastianiMorra, 1985. The present analysis increases the biostratigraphic usefulness of the group and improves taxonomic knowledge of the Neogene molluscan assemblages defined previously for Patagonia. Zygochlamys geminata is confined to the latest Oligocene-early Miocene interval of the Austral Basin of Patagonia (Argentina) and to the early Miocene of Chile, Z. jorgensis is restricted to the early to middle Miocene of the Golfo San Jorge and northern Austral Basins, and Moirechlamys n. gen., the most widespread genus, occurs in the late Miocene-early Pliocene of the Austral, Golfo San Jorge, Valdés, and Colorado basins. All these genera are endemic to southern South America; Zygochlamys is not related to other circumpolar genera such as AustrochlamysJonkers, 2003 or PsychrochlamysJonkers, 2003, rejecting its dispersal in the Antarctic Circumpolar Current, as has been proposed previously. Fil: Santelli, María Belén. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina Fil: del Río, Claudia Julia. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina